2015
DOI: 10.1111/iju.12951
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde intrarenal surgery for urinary stone disease in patients with solitary kidney: A retrospective analysis of the efficacy and safety

Abstract: Abbreviations & Acronyms Dcreatinine = change in serum creatinine level DGFR = amount of change in glomerular filtration rate CT = computed tomography eGFR = estimated glomerular filtration rate GFR = glomerular filtration rate KUB = kidney-ureterbladder PCNL = percutaneous nephrolithotomy POD = postoperative day POM = postoperative month RIRS = retrograde intrarenal surgery SFR = stone-free rate SWL = shock wave lithotripsy Objectives: To compare outcomes of retrograde intrarenal surgery for urolithiasis betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…They may cause urinary tract infection, anuria, renal insufficiency or sepsis [1]. Therefore, stones in patients with solitary kidney need active treatment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They may cause urinary tract infection, anuria, renal insufficiency or sepsis [1]. Therefore, stones in patients with solitary kidney need active treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, stones in patients with solitary kidney need active treatment. The management of stones in this cohort as yet remains a challenging scenario, complete removal of the stone and protection of the renal function through safely surgical treatments is critical [1, 2]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Ghosh and Somani showed that URS in the solitary kidney may be performed harmless as a day-case procedure [ 4 ]. In a recent study, Kuroda et al found that RIRS for <2 cm calculi in solitary kidney patients is as safe as in bilateral kidney patients [ 5 ]. Moreover, the preferred procedure is often implemented with the special concern to avoid any possible complications.…”
mentioning
confidence: 99%